Analisis Saluran Pemasaran Madu pada UMKM Lebah Madu Murni Al Halif di Manonjaya Kabupaten Tasikmalaya - Muhammad Giri Sundoro; Ristina Siti Sundari; Ulpah Jakiyah (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
Honey is a natural and usually sweet-tasting liquid manifested by honeybees (Apis sp) from plant flower juice (flower nectar) or other plant parts. Marketing channel is a flow of various institutions that perform all activities used as a tool to distribute a good and ownership that starts from the producer and ends at the end user. This research was conducted to find out and describe the honey marketing channels and analyze the efficiency of honey marketing channels in Al Halif Pure Honey Bee MSMEs in Manonjaya, Tasikmalaya Regency. This research was conducted at Al Halif Pure Honey Bee MSME in Manonjaya, Tasikmalaya Regency. The analysis method used is descriptive qualitative and quantitative analysis. The results showed that there are two honey marketing channels, namely marketing channel I: Beekeepers - Wholesalers (MSME Al Halif Pure Honey Bee)) - End Consumers and Beekeepers receive a large amount obtained is 53% of the price of the wholesaler level, marketing channel II: Beekeepers - Wholesalers (MSME Al Halif Pure Honey Bees) - Small Traders (Retailers) - End Consumers, beekeepers receive a large amount obtained is 45% of the price of the small trader level. Honey marketing channels with efficient criteria with a channel efficiency value I of 8.88% and marketing channel II of 6.8%.